Vitamin D receptor gene polymorphisms in association with diabetic nephropathy: a systematic review and meta-analysis - Lina Yang; Lan Wu; Yi Fan; Jianfei Ma (BMC, 2017)
Abstract Background A large amount of researches have demonstrated that vitamin D receptor (VDR) gene polymorphisms are associated with diabetic nephropathy (DN) risk in diabetes mellitus (DM) patients. Nevertheless, the results are inconclusive and inconsistent. Methods We screened PubMed, Embase, Chinese National Knowledge Infrastructure and Chinese Wanfang databases for those relevant studies updated in May 2016. Results 7 studies involving 2564 subjects were recruited. We evaluated the genotypic and allelic differences between DN patients and DM controls. Overall analysis showed that no significant association was found among the ApaI, BsmI, FokI,TaqI gene polymorphisms and DN susceptibility in diabetic patients (all P values > 0.05). In the stratified analysis, TT genotype was related to DN susceptibility in Asians (TT vs Tt + tt: OR =2.21, 95% CI: 1.05-4.67, p = 0.04). The sensitivity analysis showed that the results in overall populations, Caucasians and Asians were dependable. Conclusions No significant association was found among the ApaI, BsmI, FokI, TaqI polymorphisms and DN risk in overall populations, the TaqI variants might related to DN susceptibility in Asians. Further researches are required to testify our meta-analysis.